Analisis Kesesuaian Tugas Pokok dan Fungsi dengan Kompetensi Pegawai pada Dinas Kependudukan dan Catatan Sipil Kabupaten Sidrap - Syahrul S Thahir (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
In general, this research was to determine the suitability analysis of main tasks and functions against employees’ competence at the Department of Population and Civil in Sidenreng Rappang Regency. The research was based on a survey, and using a descriptive research type to describe the issues. The sampling technique used was saturated sample, obtaining primary data from interviews and questionnaires, and obtaining secondary data from related literatures, documents, and reports. The results showed several indicators from job description such as description of duties, responsibilities, authority and working conditions consisted of an absolute requirements, basic requirements, important terms, and supplemental terms. Overall results showed high compliance rate, consisting description of duties at 61,08%, responsibility at 72,37%, and authority at 77,75%. This value indicated an average of 70,40% employee at the Department of Population and Civil in Sidenreng Rappang Regency to understand the duties, responsibilities, and authorities. While the affecting factors consisted the appropriate level of knowledge at 47,37%, and unskillfulness at 55,26%.